KORELASI ASPEK KOGNITIF TERHADAP PEMANFAATAN VOLUNTARI COUNSELING TESTING (VCT) - Kusuma, M. Iqbal Angga; Noorma, Nilam; Palupi, Eva Riantika Ratna; Putri, Dwi Diana (Ensiklopedia of Journal, 2025)
Abstract: Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system, which functions to fight various infections and diseases. VCT as an early detection service for HIV / AIDS infection. The purpose of the study was to determine the correlation of cognitive aspects to the utilization of Voluntary Counseling Testing (VCT). The research design used in this study was cross sectional. The research was conducted at Padang Bulan Health Center Medan. The research was conducted in October 2024. The study population was all patients who visited and utilized Voluntary Counseling Testing (VCT) services. The sample amounted to 79 respondents. The sampling technique used in this study was purposive sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between cognitive aspects of attitude (p value: 0.000) to the utilization of VCT services. It is recommended for family members to provide support to PLWHA to utilize VCT services.Keywords: HIV, Attitudes, VCT